A multivariate assessment of offensive performance indicators in Men's Handball: Trends & Differences in the World Championships., - P Meletakos; G. Vagenas; I Bayios (International Journal of Performance Analysis in Sport, 2011)
The purpose of the present study was to assess the relative importance of selected performance indicators in modern top-level handball through the analysis of offensive actions in three consecutive men’s world championships (2005, 2007 and 2009). A total of 288 matches were examined, which included 29,439 throw attempts resulting in 16,240 goals. The results demonstrated the strong relationship between the six-meter and nine-meter offensive actions, as evidenced by their very high negative correlation coefficients in both the throw attempts and goals scored. The significant decrease of the throw attempts and goals scored from the six-meter position, evidenced in the 2007 and 2009 championships, is associated with the collateral significant increase of the nine-meter throws and goals. Interestingly, the nine-meter efficacy remained relatively constant throughout the three competition years, while the six-meter efficacy depicted a significant increase in competition years 2007 and 2009 compared to 2005, as a result of the appearance of highly qualified top ranking players in the pivot position. The high performance efficiency of these players resulted in adaptive defensive tactics to prevent the ball from reaching this key position. The present findings provide valuable information to handball coaches, in the design of their strategic and tactical plans.